2019
DOI: 10.16993/sjwop.60
|View full text |Cite
|
Sign up to set email alerts
|

Do Older Employees Suffer More from Work Intensification and Other Intensified Job Demands? Evidence from Upper White-Collar Workers

Abstract: Background: Working life today is characterized by acceleration and intensification due to social, and particularly technological, acceleration affecting the whole of society. These phenomena also affect working life by intensifying job demands, possibly imposing new job stressors on the workforce. At the same time workforce is aging, raising a question how older employees manage to cope with these work life changes. Methods: This study examined intensified job demands and their effects on occupational well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 31 publications
3
30
2
8
Order By: Relevance
“…However, this profile did not differ significantly from certain other profiles when job performance and meaning of work were analyzed as dependent variables, although belonging to this high MJDs profile predicted poorer job performance and meaning of work. These results are consistent with those of earlier studies, which have already shown that IJDs, illegitimate tasks, and interruptions at work are severe job stressors implying higher strain, e.g., job burnout, anxiety or psychosomatic symptoms (e.g., Eatough et al, 2016;Fletcher et al, 2017;Kubicek et al, 2015;Liebl et al, 2012;Semmer et al, 2015;Mauno et al, 2019b;Mauno et al, 2020). Nevertheless, in contrast to our study, these prior studies have analyzed these MJDs separately, ignoring combinations of them (profiles) and their outcomes, which we focused on.…”
Section: Implications Of Experiencing Mjdssupporting
confidence: 93%
See 3 more Smart Citations
“…However, this profile did not differ significantly from certain other profiles when job performance and meaning of work were analyzed as dependent variables, although belonging to this high MJDs profile predicted poorer job performance and meaning of work. These results are consistent with those of earlier studies, which have already shown that IJDs, illegitimate tasks, and interruptions at work are severe job stressors implying higher strain, e.g., job burnout, anxiety or psychosomatic symptoms (e.g., Eatough et al, 2016;Fletcher et al, 2017;Kubicek et al, 2015;Liebl et al, 2012;Semmer et al, 2015;Mauno et al, 2019b;Mauno et al, 2020). Nevertheless, in contrast to our study, these prior studies have analyzed these MJDs separately, ignoring combinations of them (profiles) and their outcomes, which we focused on.…”
Section: Implications Of Experiencing Mjdssupporting
confidence: 93%
“…For instance, we found a large profile (30%) where employees scored relatively high on intensified job demands (IJDs; work intensification, intensified planningand decision-making demands, and learning demands (see Kubicek et al, 2015, Mauno et al, 2019bMauno et al, 2020), but moderately on illegitimate tasks and interruptions at work (MHIJD profile). On the one hand, the dimensions of IJDs tend to correlate, but on the other hand, they are also distinguish-able constructs with different antecedents and outcomes as indicated in earlier studies (Korunka et al, 2015;Kubicek et al, 2015;Mauno et al, 2019b;Mauno et al, 2020).…”
Section: Co-occurrence Of Mjdsmentioning
confidence: 95%
See 2 more Smart Citations
“…2015;Mauno ym. 2019a, 2019b, Rosa 2003. Seuraavassa avaamme työn intensiivisyyden ilmenemismuotoja Kubicekin ym.…”
Section: Tutkimuksen Pääkäsitteet: Työn Intensiivisyys Työssä Suoriuunclassified